An Exploratory Study on the Information Needs of Prostate Cancer Patients and Their Partners - Kassianos, Angelos P.; Raats, Monique M.; Gage, Heather (My University, 2016)
The aim of this study is to explore the information needs of men with prostate cancer and their partners retrospectively at various points in the treatment process. An online questionnaire was used to collect information from men with prostate cancer and their partners about information needs, and when these developed. Readers of a Prostate Care Cookbook and members of a Prostate Cancer Charity were invited to participate: 73 men with prostate cancer and 25 partners completed the questionnaire. Responses showed that participants develop their information needs close to diagnosis. Less educated men with prostate cancer and partners developed their needs closer to the time after diagnosis than those with higher education. Partners develop an interest on information related to treatment and interaction earlier than patients. Patients prioritised treatment and disease-specific information. Patients and partners differ in how their information needs develop. Medical information is prioritized by patients as opposed to practical information by partners. Health care provision can be tailored to meet the different needs of prostate cancer patients and their partners at different times in the treatment process.
Keywords: Information needs; Family support; Partners; Prostate cancer